Indexicality in EFL Classroom Learning: A Critical Classroom Discourse Analysis - Fajar, Muh; Intakha, Alaudy Hendy; Sulistyowati, Heny (Institut Agama Islam Negeri Kudus, 2025)
This study examined dialogues between a lecturer and his students in an EFL classroom learning to find out indexicality. It employed a qualitative technique. The data were dialogues by the lecturer and his students at English Department of the higher education institution in Jombang when they were involved the learning process of the Classroom Discourse class. There were two instruments in this study, they were the researcher himself and documentation. In terms of indexicality, the participants used personal deixis o strengthen his position on the issues faced by the lecturer when the utterance is addressed and forces the audience to accept his views. In addition, the shift in deixis